Synchronous pyoderma gangrenosum and inflammatory bowel disease, healing after total proctocolectomy - Andrade, Pedro (2012)
We present a female patient observed with painful violaceous plaques with central bullae and pustules on the lower limbs, rapidly transformed into ulcers, associated with bloody diarrhea, recurrent oral erosions and hyperthermia in the previous 3 months. Cutaneous biopsy was consistent with pyoderma gangrenosum, and intestinal diagnostic procedures revealed a non-classifiable inflammatory bowel disease with high x-ANCA titers. Soon after admission the patient was submitted to total proctocolectomy following colonic perforation. Complete ulcer healing occurred three months after surgery, without recurrence. Pyoderma gangrenosum is a rare dermatosis frequently associated with inflammatory bowel disease. This case is particularly interesting for the synchronic clinical presentation of cutaneous and intestinal diseases, but also for the prompt regression of the former after total proctocolectomy.